2014
DOI: 10.1155/2014/159049
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mammographic Breast Density with Dairy Product Consumption, Sun Exposure, and Daily Activity

Abstract: Background. Mammographic density is a risk factor, for breast cancer and its association with various factors is under investigation; we carried out a study to assess its relationship with daily dairy intake, sun exposure, and physical activities. Patients and Methods. Women ≥40 years of age were interviewed about habits of dairy product consumption, daily sun exposure and physical activity. Exclusion criteria consisted of history of breast cancer, consumption of calcium and vitamin D supplements, hormone repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, this relation has been highly demonstrated for the former [ 29 ], but not in the latter condition [ 30 ]. Also, use of dairy products might lower the risk of endometriosis [ 31 ], while the few studies about the association of these products with MBD have showed controversial results from no relation to a negative association [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this relation has been highly demonstrated for the former [ 29 ], but not in the latter condition [ 30 ]. Also, use of dairy products might lower the risk of endometriosis [ 31 ], while the few studies about the association of these products with MBD have showed controversial results from no relation to a negative association [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies employing objective measures specific to high and low-fat dairy are needed to clarify these possibilities. Past work has incorporated such measures as detailed questionnaires and daily food diaries to better understand high vs. low-fat diets [39][40][41], and these same measures can be used in studies examining dairy intake, physical activity, and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…To have a greater understanding of the determinants of breast density, especially those that can be modified, studies have investigated the associations of adult diet and dietary factors with MBD. Results from those studies have, however, been largely null [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%